Microstructure determines crystallinity-driven singlet fission efficiency in diF-TES-ADT - Hoyeon Choi; Stefan Skalsky; David G. Bossanyi; Jenny Clark; Patrick Parkinson (Scientific Reports)
Abstract Singlet fission (SF) describes the conversion of a single photon-generated excited state into two triplet excitons through an initial singlet state. Despite its significance for solar energy applications, the relationship between microstructure, temperature, and SF efficiency remains poorly understood. Using cryogenic fluorescence microscopy, we correlate primary singlet fission (PSF) efficiency with local film morphology in a prototypical high-efficiency anthradithiophene (diF-TES-ADT) thin film. Our hyperspectral microscopy measurements of absorption and emission with sub-micron resolution reveal spatially inhomogeneous PSF efficiency that correlates directly with local crystallinity. Temperature- and time-resolved spectroscopy demonstrate that enhanced PSF efficiency in highly crystalline regions results from favorable endothermic alignment of a charge-transfer (CT) state. These findings emphasize how spatial inhomogeneity critically impacts SF film performance and caution against relying solely on spatially averaged metrics when evaluating SF materials.